Cooperation of Service Enterprises with Different Types of Entities in the Process of Creating Innovation - Dymitrowski , Adam (Studia Oeconomica Posnaniensia, 2014)
This paper presents the results of an investigation into the role of cooperation between service companies and different kinds of entities in the process of creating innovation. Because of the widespread activities of enterprises in foreign markets, the analysis concerns the relationships created both in local and foreign markets. Also, the analysis concerns four types of innovation: product, process, organizational and marketing. The conclusions presented in the paper have been derived on the basis of empirical research. The analysis showed that in order to create innovation it is necessary for a company to forge relation-ships with different types of entities, among which buyers play a particularly significant role.